Union parishad and poverty reduction strategies at the local level: A study of governance failure - Adhikary, Ashoke Kumar (BRAC Development Institute (BDI), BRAC University, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2010.